FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PEMBAYARAN DIVIDEN KAS (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - noviyati, Siska (Jurnal Tepak Manajemen Bisnis, 2015)
The objective of this research is to examine the influences of size firm, profitability, leverage, liquidity, and previous dividend toward dividend payout ratio.Sample of the research consist of 22 manufacturing companies that listed on Indonesia Stock Exchange since 2009 until 2013. Purposive sampling methods were used determining method. The analysis technique used here is multiple regressions.The research result showed that size firm, profitability, leverage, liquidity, and previous dividend simultaneously influence dividend payout ratio. Firm size, leverage and previous dividend have partially effect on dividend payout ratio. The other variables which are profitability and liquidity have no effect on dividend payout ratio.Keyword: size firm, profitability, leverage, liquidity, previous dividend, dividen payout ratio.